Depiction Fantasy Figure in the Novel of The Nutcracker And The Mouse King by E.T.A Houffman - Siti Azwa Artzad (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2026)
The research aims to describe fantasy of the figure in The Nutcracker and The Mouse King The subject of this research is a genre of fantasy novel entitled The Nutcracker and The Mouse King. The primary material taken of this research is The Fantasy Character internally the novel The assessment is carried out using an objective approach, namely focusing on the elements known as intrinsic elements. Intrinsic elements with an emphasis on fantasy character. Analysis is carried out by focusing on intrinsic elements with an emphasis on characters and setting. Keywords: Character, Fantasy, Nutcracker and the Mouse King, Elements of Fantasy